Structural and Content Characteristics of the Admissions Interview as a Genre of English-Language Academic Discourse - I. M. Teplygina (Дискурс, 2025)
Introduction. The growing interest of linguistics in academic discourse, a pivotal communication type in contemporary society where science and higher education are central, underscores the relevance of this study. The admissions interview, a genre intersecting educational, pedagogical, and scientific communication, remains underresearched, highlighting the study's scientific novelty. This research aims to identify and delineate the linguacultural script of the English-language admissions interview as an academic discourse genre, specifying its stages and corresponding speech act types.Methodology and sources. The study employed discursive and interpretive analysis methods. The empirical data comprised 70,000 words of admissions interview transcripts from higher education institutions, enabling a detailed examination of genre characteristics.Results and discussion. The research revealed the genre's structural and content-related features, including a six-stage linguacultural script categorized into metadiscursive (initiating, orienting, concluding) and ideational (testing, summarizing, evaluating) speech act groups. Metadiscursive acts regulate dialogue, framing communication, while ideational acts focus on content, knowledge assessment, and candidate competency evaluation. Each stage exhibits specific tactics, reflecting the genre's institutional nature and orientation towards academic values.Conclusion. The analysis confirms the admissions interview as a multi-layered genre, integrating traditional academic functions (knowledge assessment, critical thinking) with contemporary communicative practices (dialogicity, interactivity). The findings refine the genre's position within academic discourse, emphasizing its uniqueness compared to other interview types (e.g., job interviews), which prioritize experience over educational potential. The proposed methodology for analyzing stages and speech acts enriches genre theory, offering a tool for exploring other oral interactive genres and enhancing understanding of their structural and content-related specificities within sociocultural norms. The study's conclusions have practical implications for academic interview preparation and the advancement of linguacultural research.